Indeks Glikemik Bahan Makanan Dengan Kadar Glukosa Darah Pada Penderita Diabetes Mellitus Tipe 2 Di Puskesmas Ranotana Weru - Nita R. Momongan; Phembriah S. Kereh; Sasaw Sriwartini (POLTEKKES KEMENKES MANADO, 2019)
The food glycemic index is a scale or number of foodstuffs that if consumed can have an impact on blood glucose levels so it can be used as a way to control blood glucose levels. The purpose of this study to determine the relationship of glycemic index of food with blood glucose level at diabetes mellitus type 2 in working area of Ranotana Weru Health Center. This research is an observational research using cross sectional research design with sample consist of 34 respondents who fill up the criteria of inclusion and exclusion. Data retrieval is done through interviews using food frequency questionnaire form (FFQ) and blood glucose levels obtained from the examination using autocek. Univariate analysis is done by frequency distribution and bivariate analysis using Fisher’s Exact Test. The results showed that of 34 respondents most of the respondents have blood glucose levels when the uncontrolled ≥180 mg/dl and consumed a high food glycemic indexs of 28 respondents (82,3%). While respondents have controled blood glucose levels of <180 mg/dl and consumed a low food glycemic index is 5 respondents (14,7%). Average blood glucose levels of respondents is 237,74% mg/dl. The statistical test is done obtained that there was correlation of food glycemic index with blood glucose level with value p = 0,000 (p <0,05). Conclusion, there is correlation of food glycemic index with blood glucose level in type 2 diabetes mellitus in working area of Ranotana Weru Health Center.